2023
DOI: 10.1038/s41598-023-38893-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher longitudinal brain white matter atrophy rate in aquaporin-4 IgG-positive NMOSD compared with healthy controls

Abstract: We aimed to compare longitudinal brain atrophy in patients with neuromyelitis optica spectrum disorder (NMOSD) with healthy controls (HCs). The atrophy rate in patients with anti-aquaporin-4 antibody-positive NMOSD (AQP4 + NMOSD) was compared with age-sex-matched HCs recruited from the Japanese Alzheimer’s Disease Neuroimaging Initiative study and another study performed at Chiba University. Twenty-nine patients with AQP4 + NMOSD and 29 HCs were enrolled in the study. The time between magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Unlike MS, patients with NMOSD are considered to exhibit attack-dependent disability, T2 lesion volume, and neurodegeneration. Although some recent studies reported that silent progression of brain atrophy was observed in AQP4-antibody-seropositive NMOSD [ 16 , 17 ], the silent progression of extensive WMH and its clinical significance in patients with long-standing NMOSD have not been reported. The present and previous cases indicated that asymptomatic leukodystrophy-like MRI findings can be present in NMOSD and not related to a poor prognosis, although further investigations are necessary to confirm this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike MS, patients with NMOSD are considered to exhibit attack-dependent disability, T2 lesion volume, and neurodegeneration. Although some recent studies reported that silent progression of brain atrophy was observed in AQP4-antibody-seropositive NMOSD [ 16 , 17 ], the silent progression of extensive WMH and its clinical significance in patients with long-standing NMOSD have not been reported. The present and previous cases indicated that asymptomatic leukodystrophy-like MRI findings can be present in NMOSD and not related to a poor prognosis, although further investigations are necessary to confirm this conclusion.…”
Section: Discussionmentioning
confidence: 99%